2015
DOI: 10.1002/jmv.24221
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotypes distribution by cervical cytologic status among women attending the General Hospital of Loandjili, Pointe-Noire, Southwest Congo (Brazzaville)

Abstract: HPV infection is associated with cervical cancer, one of the major public health problems in developing countries. In the Republic of Congo, despite of the high age-standardized incidence rate estimated at 25.2 per 100,000 women, molecular epidemiology data on HPV infections are very limited. We investigated HPV genotypes distribution in cervical smears among patients attending the General Hospital of Loandjili, Southwest Congo. A cross-sectional hospital-based study was conducted on 321 women. Liquid-based cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
(44 reference statements)
3
15
0
Order By: Relevance
“…Previous study has confirmed that HPV infection, especially hr‐HPV, is the main cause of cervical cancer . In addition, persistent HPV infection is related to the development of cervical cancer . However, there is a contrast between different countries and areas on the genotype distribution of HPV infection .…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has confirmed that HPV infection, especially hr‐HPV, is the main cause of cervical cancer . In addition, persistent HPV infection is related to the development of cervical cancer . However, there is a contrast between different countries and areas on the genotype distribution of HPV infection .…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have confirmed that HPV infection is a causal and necessary factor for cervical cancer, 3,27,28 and persistent HPV infections in particular are primarily associated with the development of this type of cancer in women. 5 A positive HPV DNA test result in women indicates a risk of developing cervical cancer. 22 This type of cancer is considered the second most common malignancy in women worldwide and represents 9.8% of all cancer in women.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the association of HPV with cervical cancer or the risk of carcinogenesis, all HPV genotypes can be divided into different subgroups of mucosal HPVs: high‐risk types of HPVs (HR‐HPV), such as HPVs 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 68, 73, and 82, which are classified as carcinogenic to humans; low‐risk types of HPVs (LR‐HPV), such as HPVs 6, 11, 28, 32, 40, 42, 43, 44, 54, 55, 57, 61, 62, 71, 72, 74, 81, 83, 84, 86, 87, and 89; probable/possible HR‐HPVs (pHR‐HPV), such as HPVs 68, 26, 53, 66, 82, 70, 67, and 73 . The HR‐HPVs are the causes of approximately 5% of all cancers in humans and one‐third of all virus‐induced tumors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral persistence and progression towards cervical cancer may be enhanced in HPV16 variants, which may partly explain the difference in prevalence in some populations [29]. Previous studies in Gabon and in other Sub-Saharan African countries have shown the predominance of the African lineage in HSIL cases [12, 31–34]. However, our analysis of the nucleotide variation of all HPV16 sequences showed that 85.7 % of the sequences belonged to the African branch (Af1 and Af2) and 14.3 % to the European branch.…”
Section: Discussionmentioning
confidence: 99%